STRATEGI PENINGKATKAN PENGHASILAN DRIVER OJEK ONLINE DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Fajar Hasani; Haqibul Mujib (Syari'ah Economics, 2019)
This study aims to determine the risk management of murabahah financing and determine the impact of risk management implementation on murabahah financing settlement solutions. The method used in this study is a qualitative method that produces descriptive data using data collection techniques by observation, interviews, and documentaries in accordance with the title being observed. The risk of financing at BSM KCP Ciamis has two risks, namely sidestraiming or force majeure. Sidestraiming is a risk that arises from the mismatch of a customer financing request with the use of the customer's financing. Meanwhile, force majeure is the risk that arises from events outside the bank's predictions, such as natural disasters and accidents. Risk management carried out by BSM KCP Ciamis is by gathering information, collecting documents, and verifying its customers. These three steps are carried out using analysis. The analysis used by BSM KCP Ciamis is 5C analysis, namely character (character), capacity (capacity), capital (capital), collateral (guarantee), and conditions (conditions). Among the 5Cs, there are the most prioritized, namely analysis of character (character), capacity (capacity). If the customer has a problem, the bank will resolve the problem by using several methods including rescheduling, reconditioning, or restructuring. The implementation of risk management carried out by BSM KCP Ciamis can be categorized as healthy financing, because the non-performing financing is below 7%, namely 2.5%. This success is not only carried out by one party, but for the support and cooperation of all components in BSM KCP Ciamis